Quality of Life in Rectal Cancer Patients After Chemoradiation: Watch-and-Wait Policy Versus Standard Resection – A Matched-Controlled Study. Issue 10 (October 2017) - Hupkens, Britt J.P.; Martens, Milou H.; Stoot, Jan H.; Berbee, Maaike; Melenhorst, Jarno; Beets-Tan, Regina G.; Beets, Geerard L.; Breukink, Stéphanie O.
Abstract : BACKGROUND: Fifteen to twenty percent of patients with locally advanced rectal cancer have a clinical complete response after chemoradiation therapy. These patients can be offered nonoperative organ-preserving treatment, the so-called watch-and-wait policy. The main goal of this watch-and-wait policy is an anticipated improved quality of life and functional outcome in comparison with a total mesorectal excision, while maintaining a good oncological outcome. OBJECTIVE: The aim of this study was to compare the quality of life of watch-and-wait patients with a matched-controlled group of patients who underwent chemoradiation and surgery (total mesorectal excision group). DESIGN: This was a matched controlled study. SETTINGS: This study was conducted at multiple centers. PATIENTS: The study population consisted of 2 groups: 41 patients after a watch-and-wait policy and 41 matched patients after chemoradiation and surgery. Patients were matched on sex, age, tumor stage, and tumor height. All patients were disease free at the moment of recruitment after a minimal follow-up of 2 years. MAIN OUTCOME MEASURES: Quality of life was measured by validated questionnaires covering general quality of life (Short Form 36, European Organization for Research and Treatment of Cancer QLQ-C30), disease-specific total mesorectal excision (European Organization for Research and Treatment of Cancer QLQ-CR38), defecation problems (Vaizey and low anterior resection syndrome scores), sexual problems (International Index of Erectile Function and Female Sexual Function Index), and urinary dysfunction (International Prostate Symptom Score). RESULTS: The watch-and-wait group showed better physical and cognitive function, better physical and emotional roles, and better global health status compared with the total mesorectal excision group. The watch-and-wait patients showed fewer problems with defecation and sexual and urinary tract function. LIMITATIONS: This study only focused on watch-and-wait patients who achieved a sustained complete response for 2 years. In addition, this is a study with a limited number of patients and with quality-of-life measurements on nonpredefined and variable intervals after surgery. CONCLUSIONS: After a successful watch-and-wait approach, the quality of life was better than after chemoradiation and surgery on several domains. However, chemoradiation therapy on its own is not without long-term side effects, because one-third of the watch-and-wait patients experienced major low anterior resection syndrome symptoms, compared with 66.7% of the patients in the total mesorectal excision group. SeeVideo Abstract athttp://links.lww.com/DCR/A395 .